Pemberdayaan Masyarakat Desa Melalui Teknologi Foam Mat Drying Sebagai Alternatif Pengolahan Jeruk Siam (citrus nobilis) di RW 07 Desa Mundurejo Umbulsari Jember - Eko Wiyono, Andi; Herlina, Herlina; Rahayu, Supratiana (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Mundurejo Village is one of the villages located in the westernmost region of Umbulsari District, Jember Regency which has quite a large local fruit potential, namely Siamese oranges (citrus nobilis). Foam Mat Drying technology can be used as a new breakthrough for processing Siamese oranges into powdered drinks. The approach used in this service is the Participatory Rural Appraisal (PRA) method. This approach emphasizes the involvement of target communities in activities as a whole, both individually and in groups. The results of local fruit processing are expected to have high added value. In general, partners understand and can practice foam mat drying technology well.